DENOSUMAB-RELATED OSTEONECROSIS OF THE JAWS: A CASE REPORT - Milena Petkova; Pavel Stanimirov (Peytchinski Publishing, 2017)
Bisphosphonates are potent and effective drugs frequently used to prevent the skeletal complications associated with postmenopausal osteoporosis in women, to manage patients with multiple myeloma, hypercalcemia, and metastasis of cancer to the bone. The search for new medications with the same therapeutic effectiveness as the bisphosphonates but fewer side effects has resulted in the discovery of Denosumab, a human monoclonal antibody against the receptor activator for nuclear factor kappa B ligand (RANKL), therefore inhibiting osteoclast differentiation and function. Denosumab is a class of drugs that are entirely different from the traditional antiresorptive drugs, the bisphosphonates. Denosumab has several advantages, including better tolerability, ease of subcutaneous injection, a shorter half-life, and a reduced incidence of nephrotoxicity. Patients receiving bisphosphonates are at risk to develop a severe devastating complication - osteonecrosis of the jaws (ONJ) - which is challenging to treat. Since 2010 there have been reports of ONJ in patients taking denosumab. In the 2014 position paper of the American Association of Oral and Maxillofacial Surgeons, the nomenclature "bisphosphonate-related osteonecrosis of the jaw" was changed to "medication related osteonecrosis of the jaw" (MRONJ). The change is justified to accommodate the growing number of osteonecrosis cases involving the maxilla and mandible associated with other antiresorptive (denosumab) and antiangiogenic therapies. Here we report a development of denosumab-related osteonecrosis of the jaw (DRONJ) - a new type of bony necrosis- in patient with bone metastases of breast cancer on Denosumab therapy. The patient has no previous history of taking bisphosphonates.